Just Wars Theory as a Key Element of Germany’s New Sonderweg - Kashnikov, Boris; Glaser , Marina (Conatus - Journal of Philosophy, 2023)
The article traces the evolution and key characteristics of the German Sonderweg – Germany’s special path starting from the end of the 19th – the middle of the 20th century. The article considers geopolitical, ideological, and historical reasons for its emergence, transformation, and the specificity of its normative constitution, designed to morally justify the use of military force as an indispensable lever for Germany to achieve its goal of creating a “German Europe.” We develop a hypothesis of a possible remake at the beginning of the 21st century of a new German Sonderweg, focused on creation of the “European Germany,” stemming from liberalism and just war theory. It is demonstrated that Zeitenwende, announced in 2022, facilitated the possible resort to arms and made militant solution of political dilemmas a reality again. The discourse analysis of the German political speeches makes it possible to claim that the political elites in Germany are preconcerted with normative justification of the possible war. The article considers two major lines of transformation of the contemporary just war theory and their possible implication in the German military and defense policy. One of these is the emergence of human rights paradigm of the just war doctrine, another – the growing tendency of the theory to stick to national cultural tradition instead of moral universalism. The combination of the two tendencies may trigger an array of very special and unpredictable normative developments of the military policy in Germany. The further movement alongside the idea of jus ad bellum may provoke specific national perceptions of the justice of the war, which may merge the idea of just war with traditional German realism if not militarism. This tendency may lure Germany into a trap of, what we term, “human rights militarism.” To what extent the trap is viable depends on the normative constitution of the key elements of Sonderweg.